Social computing for internet addiction disorder analysis from a psychological perspective. (2017) - Huang, Mu-Jung; Chen, Mu-Yen; Cheng, Chin-Chun
This study adopts needs theory and affective ambivalence to explore how people obtain psychological satisfaction through internet usage, and to explore how such usage behaviour can lead to the development of a sense of dependence. Few previous studies have incorporated these four perspectives. Data mining techniques are used to identify association rules between needs theory, affective ambivalence, internet use behaviour and internet addiction. This study distributed paper-based and electronic questionnaires, receiving a total of 502 valid responses for a valid response rate of about 88%. From the affective ambivalence perspective, we found that emotional state varies with behaviour and age, leading to different patterns of personal expression and creativity. In addition, empirical results show our findings are consistent with Maslow's hierarchy of needs in that people only seek to address their higher-order needs once their lower-order needs are satisfied. Thus, once internet users have satisfied their needs for security, their attention then turns to demands for social interaction and self-esteem.